Viroid quasispecies revealed by deep sequencing - Brass, Joseph R J; Owens, Robert A; Matoušek, Jaroslav; Steger, Gerhard (RNA biology, 2017)
Viroids are non-coding single-stranded circular RNA molecules that replicate autonomously in infected host plants causing mild to lethal symptoms. Their genomes contain about 250-400 nucleotides, depending on viroid species. Members of the family Pospiviroidae, like the Potato spindle tuber viroid (PSTVd), replicate via an asymmetric rolling-circle mechanism using the host DNA-dependent RNA-Polymerase II in the nucleus, while members of Avsunviroidae are replicated in a symmetric rolling-circle mechanism probably by the nuclear-encoded polymerase in chloroplasts. Viroids induce the production of viroid-specific small RNAs (vsRNA) that can direct (post-)transcriptional gene silencing against host transcripts or genomic sequences. Here, we used deep-sequencing to analyze vsRNAs from plants infected with different PSTVd variants to elucidate the PSTVd quasipecies evolved during infection. We recovered several novel as well as previously known PSTVd variants that were obviously competent in replication and identified common strand-specific mutations. The calculated mean error rate per nucleotide position was less than [Formula: see text], quite comparable to the value of [Formula: see text] reported for a member of Avsunviroidae. The resulting error threshold allows the synthesis of longer-than-unit-length replication intermediates as required by the asymmetric rolling-circle mechanism of members of Pospiviroidae.
Keywords: RNA virová; sequencing error; viroidy; genom virový; mutace; sequence network mapping; Error rate; viroid-specific small RNA; Pospiviroid; reassortantní viry; Virus Replication; Genome, Viral; error threshold; Viroids; replikace viru; vysoce účinné nukleotidové sekvenování; RNA, Viral; High-Throughput Nucleotide Sequencing; quasispecies; Mutation; Reassortant Viruses